Effect of feeding two types of local fishmeal rations on Broiler performance - Ramkumar, S.; Sinniah, J.; Samarasinghe, K.; Anand Kumar, S. (My University, 2022)
Current study was conducted to find out the possibility of using two types of local fish meals as animal protein sources in broiler rations. Ninety-nine unsexed day-old broiler chicks of Hubbard Flex strain were randomly allocated to three dietary treatments each having three replicates of eleven chicks per replicate in a completely randomized design (CRD). Diets 1 and 2 contained 2.5 % of locally produced Heteropneustes fossilis (Stinging catfish) fish meal and Spilotichthys pictus (painted sweetlips) fish meal, respectively while diet 3 was a commercial feed containing imported fish meal. During the first 14 days, all the chicks were fed with a commercial broiler starter ration. From day 15 until 42 days, birds were fed with experimental diets ad-libitum. Feed intake and weight gain per bird in g/day for the dietary treatments diet 1, diet 2 and diet 3 were 89.00±2.54, 92.95±2.64, 100.56±4.66 and 50.34±1.48, 53.85±2.53 and 60.39±2.99, respectively. Diets with local fish meal recorded lower feed intake and weight gain compared to diet 3 (P<0.01). Higher feed intake and weight gain were recorded for diet 2 than for diet 1. Diet 2 recorded the highest profit per kg of carcass weight (Rs 103.37±2.80) (P< 0.02) while the differences between diet1 (Rs 93.78±3.00) and diet 3 (Rs 93.69±1.89) were not significant. As far as the cost of production per kg of carcass weight is considered diet 2 recorded the least cost (Rs 326.64 ± 2.79) (P< 0.01) while the differences between diet 1 (Rs 335.28±4.10) and diet 3 (Rs 336.50 ± 1.89 were not significant. Diet 2 was the most profitable treatment. It could be concluded that poultry feed formulated with 2.5% painted sweetlips fish meal or stinging catfish fish meal instead of commercial feed with the imported fish meal can be fed to broilers successfully and can make more profit. Painted sweetlips fish meal was better than stinging catfish fish meal in terms of broiler performance and profits. In addition, this will pave the way to make use of the trash fish which are mostly wasted otherwise and open up employment opportunities for the people involved in the value chain of broiler feed or broiler industry.
Keywords: Broiler; Cost; Imported fish meal; Painted sweetlips; Stinging catfish